Early diagnosis and management of esophageal leakage after peroral endoscopic myotomy for achalasia - Zhang, Yi-Qun; Yao, Li-Qing; Xu, Mei-Dong; Li, Quan-Lin; Chen, Wei-Feng; Hu, Jian-Wei; Cai, Ming-Yan; Qin, Wen-Zheng; Zhou, Ping-Hong (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: To improve the understanding of esophageal leakage after peroral endoscopic myotomy (POEM). Materials and Methods: From August 2010 to April 2013, patients with postoperative esophageal leakage were identified from the database of cases with achalasia who had undergone POEM and their medical records were reviewed. Results: Three patients (0.4%, 3/679) developed esophageal leakage after POEM. All three patients had non-severe chest or upper abdominal pain within 3 days after the procedure. Infections were observed, and computed tomography scans showed pleural effusion in all three patients. Pneumonia occurred in two of the three patients. Esophageal leakage was confirmed by gastroscopy. Incision rupture due to an early breaking-off of the clips at the tunnel entry was revealed in two cases. When detected, the entry was immediately closed using metal clips. A thoracic drain was placed in all cases. An enteric feeding tube was also placed to help correct nutrition deficiencies. Successful leakage closure was achieved in all three cases and no surgical intervention was needed. Conclusion: Early diagnosis and treatment can improve the status of patients with esophageal leakage after POEM and can shorten the recovery time.